Analisis Kritis Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Terhadap Keberlangsungan Demokrasi dan Generasi Muda Indonesia - Afriman Oktavianus; Ricci Otto F Sinabutar; Risma Rachmawati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
General elections are an important foothold in the contemporary democratic system. Elections are a tangible form of procedural democracy, although democracy is not the same as elections, but elections are one of the most important aspects of democracy that must also be held democratically. Material test of Article 169 letter q of Law Number 7 of 2017 concerning General Elections against Article 28D of the 1945 Constitution of the Republic of Indonesia to the Constitutional Court. Identification of the problem, namely how to consider the legal pros and cons of the Constitutional Court's decision Number 90/PUU-XXI/2023 and what are the implications of the Constitutional Court's decision on the development of Indonesian democracy. The purpose of the study is to answer the problem identification, namely to find out the legal considerations of the pros and cons of the Constitutional Court's decision Number 90/PUU-XXI/2023 and to find out the implications of the Constitutional Court's decision on the development of Indonesian democracy. The research method used is a normative juridical research method and the nature of this research is descriptive and qualitative. Article 28D paragraph (3) of the 1945 Constitution states that "Every citizen has the right to equal opportunities in government". This must be in line with the theory of distributive justice. The Constitutional Court's decision violates Sapta Karsa Hutama, the Principle of Propriety, the Principle of Non-Partiality, the Principle of Independence, the Principle of Integrity and Courtesy. However, the decision remains valid because the nature of the Constitutional Court's decision is final and binding. As a conclusion in this study, the Constitutional Court Decision is considered in accordance with the principle of distributive justice by adding experience in office as a condition so that it can produce leaders who are more prepared and competent in facing government challenges.